Periodontitis Induced by P. gingivalis-LPS Is Associated With Neuroinflammation and Learning and Memory Impairment in Sprague-Dawley Rats - Hu, Yi; Li, Huxiao; Zhang, Jing; Zhang, Xu; Xia, Xinyi; Qiu, Che; Liao, Yue; Chen, Huiwen; Song, Zhongchen; Zhou, Wei (Frontiers in Neuroscience, 2020)
Background: Periodontitis is one of the most common oral diseases and is a potential risk factor for systemic diseases. In this study, we aimed to investigate the association between periodontitis and cognitive impairment. Materials and Methods: We established a chronic periodontitis model by topical application of Porphyromonas gingivalis lipopolysaccharide (P.gingivalis-LPS) into the palatal gingival sulcus of 10-week-old male rats for a 10-week period. We assessed alveolar bone resorption using micro–computed tomography analysis and cognitive function using the Morris water maze test. We determined the levels of cytokines (interleukin [IL]-1β, IL-6, IL-8, and IL-21) and LPS in the peripheral blood/cortex, as well as toll-like receptor 4 (TLR4)/NF-κB signaling pathway activation, using reverse transcription-polymerase chain reaction (RT-PCR), enzyme-linked immunosorbent assay (ELISA), and western blot. We determined microglial/astrocyte activation, expression of Aβ1-42/APP and Tau by immunohistochemistry. Finally, we measured the expression of amyloid precursor protein (APP) and its key secretase, as well as the Aβ1-40/1-42 ratio, by RT-PCR, western blot, and ELISA. Results: We found that chronic periodontitis induced learning and memory impairment in the rats. Further, we observed that it induced significant alveolar bone resorption. There was an increase in the levels of inflammatory cytokines and LPS. Moreover, we confirmed TLR4/NF-κB signaling pathway activation. We also observed activated microglia and astrocytes with enlarged cell bodies and irregular protrusions. Finally, we observed the promotion of β- and γ-secretase APP processing. Conclusions: Our findings indicated that periodontitis was associated with learning and memory impairment, probably induced by neuroinflammation via activating the TLR4/NF-κB signaling pathway. Furthermore, abnormal APP processing could be involved in this progress.